Comparativo de trece líneas y cuatro variedades de arroz (Oryza sativa L) bajo riego en Yurimaguas - Escudero Saldaña, Alex (2007)
The present thesis was carried out in Investigación Yurimaguas's Center -IIAP, former Experimental station San Ramón, district of Yurimaguas, Prov. of High Amazons and Dpto. of Loreto. Whose coordinated geographical they are south latitude 5° 54 ', longitude west 76° 5 ' and altitude of 182 m.s.n.m, located in the left margin of the river Shanusi. The floor of controls fertility, it is a terrace low being adapted for the cultivation of the Ruffles. The comparative rehearsal, they conformed i t thirteen (13) lines (07 national and 06 introduced of the CIAT Colombia) compared with 4 varieties: Huallaga INIA, Capirona, Future 95 and INIA 14. The objective was to select promissory lines with high yield potential; in the analysis of data, the Design of Complete Blocks Randomizados the Multiple Test of DUNCAN with a probability of 5%. The main registered evaluations were: The yield in shell, macollos number for m2, number of cobs for m2, number of full and vain grains fer cob, weight of 1000 grains, days (floración and it harvests), quality molinera, and reaction to Poryzae. According to the obtained results, you conclude that the CT 10310-15-1-M-YAl-EPl {T3) with 7,450 T/ha, CNAX 5070-16-11-2b-M-YA1-EP1 (T2) with 6,401 T/ha, CT-10323-12-5-M-YAl-EPl (Tl) with 6,139 T/ha and PNA 1989-AM-F4-12-EP1 (TlO) with 6, 031 T /ha they plows promissory lines for the high reached yields, with characteristic agronomic desirable, high yield miller and lightly resistant to Pyricularia oryzae. Into same way, they plow favorable economically for the relationship bigger benefits/costo that I am bigger that the unit and very profitable when overconring 46% of profitability.